STRATEGI BERTAHAN HIDUP RUMAH TANGGA NELAYAN TRADISIONAL DALAM MENGATASI KEMISKINAN (Studi Kasus Pada Desa Bagan Cempedak Kecamatan Rantau Kopar Kabupaten Rokan Hilir) - Syuryani "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is in the background by the poverty of traditional fishermen in Bagan Cempedak Village. Traditional fishermen who use only canoes and paddles to search for fish are unable to compete with modern fishermen using motorized boats with sophisticated fishing gear, to meet the needs of traditional fisherman life doing side job which is done by every family member of traditional fisherman. With the formulation of the problem to know the socio-economic condition of traditional imagery at the present time and to know the strategy in the household of traditional fishermen in fulfilling their life needs. The theory used is the economic moral theory of farmer James C.Scott. This research uses descriptive Quantitative research method, where the population and samples taken in homogeneous. The sampling technique is Simple Random Sampling, the researcher gives the same right to each subject to get the chance to be selected as sample, with the number of traditional fisherman 42 respondents. From the results of research in the field that the socio-economic conditions of traditional fishermen in the Village Bagan Cempedak at the present time is very concern low their income due to technological limitations, low education and lack of capital and fishing equipment is very simple to make them have to work harder for their needs of life Fulfilled, and the traditional household fishermen's strategy is to do such as active, passive / reducing strategy and network strategy. Active is to increase or extend working hours, passive / reduces the reduced expenditure when fish miss the fish and do not save when the season is difficult at work, and network strategy is to lend to neighbors relatives or with toke, and owe to as business capital by traditional fishermen So that poverty in their household can be overcome. Then the reason for the fisherman to survive working as a traditional fisherman is due to low education, difficulty finding jobs, and old age who can not work hard.Keywords: Poverty, Traditional Fisherman, Strategy Survive